2018
DOI: 10.1590/s1679-45082018ao4137
|View full text |Cite
|
Sign up to set email alerts
|

Sericin and swimming on histomorphometric parameters of denervated plantar muscle in Wistar rats

Abstract: ObjectiveTo analyze the combined effects of the silk protein sericin and swimming exercise on histomorphometry of the plantar muscle in Wistar rats.MethodsForty adult rats were randomly allocated into 5 groups comprising 8 animals each, as follows: Control, Injury, Sericin, Swim, and Swim plus Sericin. Three days after crushing of the sciatic nerve the rats in the Swim and Swim plus Sericin Groups were submitted to swimming exercise for 21 days. Rats were then euthanized and the plantar muscle harvested and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Based on the morphological analysis, it was possible to notice that G2, G3, and G4 underwent characteristic changes of muscle injury and that there was no return to normal muscle properties compared to the control group. The normal morphology of muscle fibers is described as multinucleated polygonal cells, with the nuclei positioned in the periphery 1,17 , similar to what was found in the control group. In the nerve-damaged groups, some cells with amorphous shape and globose nuclei were found, some of them inside the sarcoplasmic membrane.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Based on the morphological analysis, it was possible to notice that G2, G3, and G4 underwent characteristic changes of muscle injury and that there was no return to normal muscle properties compared to the control group. The normal morphology of muscle fibers is described as multinucleated polygonal cells, with the nuclei positioned in the periphery 1,17 , similar to what was found in the control group. In the nerve-damaged groups, some cells with amorphous shape and globose nuclei were found, some of them inside the sarcoplasmic membrane.…”
Section: Discussionsupporting
confidence: 73%
“…Regarding morphometric analysis, by the measurements of area and smaller diameter, it is evident that all injury groups presented atrophy of muscle fibers. Santana et al 1,15 observed, in a similar model of nerve injury, muscle fibers characteristics of tropism, with reduction in strength and phenotypic changes. In our study, only the group using 830 nm obtained a higher result than the injury group for the area of muscle fibers, observing a small evolution.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…There is currently no consensus on the optimal use of kinesiotherapy. The most recent and popular methods that have demonstrated a positive effect of preserving and increasing muscle mass in conditions associated with the impossibility of voluntary contraction (peripheral nerve or spinal cord injuries) and degenerative changes leading to atrophy (senile sarcopenia) are passive repetitive muscle stretching (Wang et al., 2021), passive training (Shiyang et al., 2020), passive locomotor training (Hadj-Saïd et al., 2012), range of motion exercises (Rahiminezhad et al., 2022), resistance training (Messi et al., 2016), high-intensity interval training (Tayebi et al., 2019) and swimming (Santana et al., 2018). These are home-based protocols with varying frequencies, from once to twice a week, three to four times a week, to daily sessions.…”
Section: Passive Muscle Movements Exercises and Muscle Massagementioning
confidence: 99%